Study of Bottom Sediments of the Chiryurt Reservoir, Dagestan, Russia with a View to their Utilisation in Land Reclamation following Anthropogenic Interference - A. O. Omarov; G. M. Abakarov; N. S. Magomedeminov (Юг России: экология, развитие, 2020)
Aim. To study the physicomechanical and physicochemical properties of bottom sediments of the Chiryurt Reservoir, Kizilyurtovskiy District, Republic of Dagestan, Russia with a view to their possible utilisation as building materials for the production of certain grades of concrete and road asphalt-concrete, as well as for the preparation of soil substrate and as additives to potassium and phosphate mineral fertilizers.Material and Methods. The bottom sediments of the Chiryurt Reservoir, taken from different depths and different reservoir locations, were studied by spectrophoto-metric and granulometric methods.Results. The study identified: particle size distribution of samples of bottom sediments; humus content; soil fertility elements: potassium, nitrogen, phosphorus as well as heavy metal content.Conclusions: 1. Analysis of the bottom sediment samples indicates that the soil fertility elements potassium, nitrogen, phosphorus are not sufficient for them to be used as an independent fertilizer, although they might perhaps be used as an auxiliary additive to a principal fertilizer. The levels of toxicity of heavy metals were found to be very low - much lower than the Maximum Allowable Concentrations. 2. The sediments could be used as soils for the reclamation of land after anthropogenic interference (e.g. after a quarry has been excavated for brick production, after excavations during road construction of roads), for the modification of vertical terrain in settled areas, for landscaping, etc. 3. According to the granulometric analysis of the material composition of the samples, the bottom sediments are 85-90% composed of clay particles (thus there is no need to undertake procedures to separate out the sand fraction). 4. Since peat deposits are present in the bottom sediments of the reservoir, it makes sense to separately assess their volumes for independent development for use as fertilizer for the re-cultivation of floodplain lands.